Subtelomeric I-SceI-Mediated Double-Strand Breaks Are Repaired by Homologous Recombination in Trypanosoma cruzi - Chiurillo, Miguel A.; Moraes Barros, Roberto R.; Souza, Renata T.; Marini, Marjorie M.; Antonio, Cristiane R.; Cortez, Danielle R.; Curto, María Á.; Lorenzi, Hernán A.; Schijman, Alejandro G.; Ramirez, José L.; da Silveira, José F. (Frontiers in Microbiology, 2016)
Trypanosoma cruzi chromosome ends are enriched in surface protein genes and pseudogenes (e.g., trans-sialidases) surrounded by repetitive sequences. It has been proposed that the extensive sequence variability among members of these protein families could play a role in parasite infectivity and evasion of host immune response. In previous reports we showed evidence suggesting that sequences located in these regions are subjected to recombination. To support this hypothesis we introduced a double-strand break at a specific target site in a T. cruzi subtelomeric region cloned into an artificial chromosome (pTAC). This construct was used to transfect T. cruzi epimastigotes expressing the I-SceI meganuclease. Examination of the repaired sequences showed that DNA repair occurred only through homologous recombination with endogenous subtelomeric sequences. Our findings suggest that double-strand breaks in subtelomeric repetitive sequences followed by homologous recombination between them may contribute to increased variability in T. cruzi multigene families.